Computational Design, Organic Synthesis, and Biological Evaluation of Polyphenol Proteasome Inhibitors: Significance in Drug Discovery and Cancer Prevention - Daniel, K. G.; Chan, T. H.; Dou, Q. P. (Drug Design Reviews - Online (Discontinued), 2005)
Human tumor cell growth depends on the ubiquitin/proteasome degradation pathway. This pathway is essential in promotion of tumor cellular proliferation, inhibition of programmed cell death (apoptosis), and development of drug resistance, suggesting that proteasome inhibitors could be developed as potential novel anticancer drugs. This hypothesis has been supported by both experimental and clinical results. Most recently, green tea polyphenols (GTPs) containing an ester bond have been identified as a new class of proteasome inhibitors. A mechanistic model to account for the inhibition of proteasome by GTPs has been proposed, evaluated using in silico docking calculations, and validated by comparison of predicted and actual activities of naturally occurring or synthesized GTP analogs. In this review, by following the development of GTPs, traditional methods of drug discovery will be examined including purification and enzymeinhibitor crystal structures. Furthermore, newer techniques such as computational modeling and docking will be evaluated with regards to integration with more traditional approaches. This review will use polyphenol proteasome inhibitors as an example to critically examine the development cycle of drug discovery from compound design, to organic synthesis, to chemical characterization, and then to biological evaluation.
Keywords: prevention